Reducing poverty through integrated management of groundwater and surface water - International Water Management Institute; Global Water Partnership (International Water Management Institute, 2005)
The full poverty-fighting potential of existing irrigation schemes is not being realized?largely because of inequitable water distribution and unsustainable land and water management practices. An integrated water resources management (IWRM) approach reveals opportunities to reduce poverty and improve overall agricultural productivity and sustainability in these systems. Research in India and Pakistan has highlighted one such opportunity?integrated management of surface water and groundwater?that has great potential for water-short systems with variable groundwater resources. By considering groundwater availability and quality when allocating surface water, water managers could improve the situation of millions of poor farmers with inadequate access to both surface water and groundwater and overall productivity in irrigated systems. The prevailing fragmented approach?where groundwater and surface water are managed separately?has contributed to high vulnerability and low agricultural productivity for farmers in the tail ends of canals and to land salinization in areas with poor quality groundwater.